APPLICATION OF THINK PAIR SHARE (TPS) MODEL TO IMPROVE STUDENT LEARNING OUTCOMES IN PANCASILA AND STATE EDUCATION (PPKN) LESSONS (IN MTS HIDAYATUS SHIBYAN PARIT NA’IM KABUPATEN KUBU RAYA) - Syaifurrahman, Syaifurrahman; Rosyid, Sulistyarini; Rosyid, Rum (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe title of this research is